Los cuentos como estrategia para incentivar el desarrollo de valores - Castañeda Rodríguez, Alicia Esther (2021)
Currently in our society there is a loss of values due to many factors, including family, social, _x000D_ economic and educational. It can be observed that in Educational Institutions the basic values _x000D_ are not being properly practiced, such as respect, responsibility, punctuality, among others, _x000D_ leading to the exercise of anti-values. Therefore, the study objective of this work is the use _x000D_ of children's stories as a didactic resource for the development of values in students; as well _x000D_ as communication skills at the primary level. This work is based on Ausubel's Reception _x000D_ Learning Theory, where the student must learn the content that he is asked to understand and _x000D_ incorporate into his cognitive structure and then reproduce it and relate it to other learning _x000D_ and subsequently solve future problems. Likewise, it is also based on the theory of Teun Van _x000D_ Dijk, who maintains that the different texts all differ from each other, not only because of _x000D_ their different communicative and social functions that they can emit to the reader, but that _x000D_ they have different types in their construction, it is for that reason that; Children have been _x000D_ able to interact with various texts, including children's stories where children can understand _x000D_ them and later produce a text. Finally, this research work aims to propose the use of stories _x000D_ as a strategy to improve the communication skills of 1st grade students of the Educational _x000D_ Institution No. 80089 - "Señor de Huamán" of primary education and especially at _x000D_ cultivation of values that are being lost today. Likewise, it can also be used as a reference _x000D_ for further studies.